Asthma patients hospitalized with influenza lack mucosal and systemic type 2 inflammation - Jha,A; Dunning,J; Tunstall,T; Hansel,T; Openshaw,PJ (European Respiratory Society, 2016)
Background: Asthmatic persons tend to suffer from severe influenza, but the reasons for enhanced severity are unknown. Objectives: To determine the clinicopathological correlates of this susceptibility, we examined nasal and systemic immune responses in adults admitted to hospital with influenza-like illnesses. Methods: We studied 210 patients admitted with influenza-like illness at 11 hospitals in the UK across 2 winter seasons (2009/10 and 2010/11). Of these, 133 (63%) had confirmed influenza and 40/133 (30%) were asthmatic. We measured a panel of cytokines and chemokines in serum and nasal mucosal lining fluid and compared results in asthmatics, non-asthmatics and healthy control volunteers. Results: Asthma patients were more often female than non-asthmatics (70% vs 39% respectively), required less mechanical ventilation (15% vs 37.6%) and had shorter hospital stays (mean 8.3 vs 15.3 days, all P <0.05). Despite having equivalent nasopharyngeal influenza viral load, asthmatics had higher serum IFN-α levels but lower serum TNF-α, IL-5, IL-6 and CXCL8 (all P<0.05). In the nasal mucosa, asthmatics and non-asthmatics had comparable levels of soluble mediators. In particular, asthmatics showed no evidence of increased type 2 inflammation (IL-5 and IL-13) or deficient interferon responses. Conclusions: Adult asthmatics hospitalised with influenza show a propensity to be female with markedly reduced morbidity and systemic inflammation than non-asthmatics. Against expectation, asthmatics did not have increased type 2 inflammation. This study highlights the importance of defining underlying immune responses to infection in individual patients to enable future delivery of personalized therapy.